PENGARUH PENGGUNAAN APLIKASI EDUDIN TERHADAP HASIL BELAJAR SISWA PADA MATERI PRAKTIK EKONOMI ISLAM KELAS XI SMAN 1 MALANG - Alfian Fahmi Abdillah; Lia Nur Atiqoh Bela Dina; Indhra Mustofha (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Learning media is used as an attraction for students' attention that canstimulate the mind. Media is needed to facilitate educators in delivering material.Especially during the Covid-19 pandemic, learning takes place online in variousschools. In connection with the new policy imposed by the government calledLimited Face-to-face Learning. For that we really need learning media that canbe used to streamline the results of student learning, both those who study inclass and those who study at home. The Edudin application is used at SMAN 1Malang, especially in class XI as a medium in carrying out PAI and Budi Pekertilearning activities, especially in the material of Islamic Economics Practice. Todetermine the effect of this application on student learning outcomes, theresearch was conducted using a quantitative study of Quasi ExperimentalNonequivalent Control Group Design. To analyze the post-test data from 66students of class XI using the Mann-Whitney U theory which is used when thedata is not normally distributed. With the final result Asymp.Sig value <0.05, thealternative research hypothesis is accepted. So that the Edudin Applicationaffects the Class 11 Student Learning Outcomes.